Optimism and mental health in college students: the mediating role of sleep quality and stress - Lai, Yun-Ju; Tsai, En-Yun; Jarustanaput, Ploypapus; Wu, Yi-Syuan; Chen, Yi-Hau; O’Leary, Samantha E.; Manachevakul, Sumatchara; Zhang, Yuan; Shen, Jiabin; Wang, Yan (Frontiers in Psychology, 2024)
Objective: College students showed a high prevalence of stress, anxiety, and depression, with medical and nursing students experiencing particularly elevated levels of mental health challenges.Optimism significantly influences overall well-being by promoting a healthy lifestyle and cognitive responses. However, the association of optimism with sleep quality, stress, and mental health in college students remains unexplored. This study aimed to (1) explore the associations of optimism with sleep quality, stress, and mental health and (2) ascertain whether sleep quality and stress mediate the association between optimism and mental health among college students.A cross-sectional study was conducted using online surveys with students from health science majors at a public university in the northeast U.S. from September to December 2022. A total of 222 students participated in the study, providing data on sociodemographics, optimism, sleep quality, stress, anxiety, and depression. Parallel and serial mediation models were utilized to examine the potential mediating roles of sleep quality and stress in the association between optimism and mental health. Results: The study found that optimism influences anxiety and depression through both direct and indirect pathways. In line with predictions, the parallel mediation analysis revealed that the impact of optimism on anxiety (βtotal = -0.598, 95% confident interval [CI]: -0.778 to -0.392) and depression (βtotal = -0.724, 95% CI: -0.919 to -0.519) was mediated by stress and sleep quality. Furthermore, the serial mediation models revealed that stress and sleep quality co-mediated the relationship between optimism and anxiety (indirect effect [IE] = -0.074, 95% CI: -0.135 to -0.029) or depression (IE = -0.084, 95% CI: -0.142 to -0.036) in a sequential manner. Conclusion: Optimism was negatively correlated with poor sleep quality, stress, anxiety, and depression. Enhanced optimism was linked to high sleep quality and less stress, anxiety, and depression. These insights emphasize the potential for school-based optimism interventions to improve sleep quality, ameliorate stress-related concerns, and alleviate mental health challenges in college students.